Los cazadores-recolectores y las plantas en Patagonia. Perspectivas desde el sitio cueva Baño Nuevo 1, Aisén - Belmar, Carolina (Social-ediciones, 2019)
The Baño Nuevo 1 cave is a unique and relevant archaeological site for the study of the regional prehistory of Aisén, from the Patagonia and the South American region, particularly for the set of human burials deposited during the Early Holocene and its long occupational sequence. In this study, the significance of the archaeobotanical record is assessed of Baño Nuevo 1, from a combination of the macro and microscopic lines of evidence, highlighting its contribution to archaeological information discussing plant supply strategies and their uses among the steppe hunter-gatherer groups settled in the place for more than seven thousand five hundred years. Carolina Belmar, Archaeologist specialized in Archeobotany, presents her new book, in which she addresses the Uses given to plants by hunter-gatherer groups settled for more than 7,500 years in the Baño Nuevo 1 cave in the Aisén region, Chile.